The glial response to intracerebrally delivered therapies for neurodegenerative disorders: is this a critical issue? - Cicchetti, Francesca; Barker, Roger A. (Frontiers in Pharmacology, 2014)
The role of glial cells in the pathogenesis of many neurodegenerative conditions of the central nervous system (CNS) is now well established (as is discussed in other reviews in this special issue of Frontiers in Neuropharmacology). What is less clear is whether there are changes in these same cells in terms of their behaviour and function in response to invasive experimental therapeutic interventions for these diseases. This has, and will continue to, become more of an issue as we enter a new era of novel treatments which require the agent to be directly placed/infused into the CNS such as deep brain stimulation, cell transplants, gene therapies and growth factor infusions. To date, all of these treatments have produced variable outcomes and the reasons for this have been widely debated but the host astrocytic and/or microglial response induced by such invasively delivered agents has not been discussed in any detail. In this review, we have attempted to summarise the limited published data on this, in particular we discuss the small number of human post-mortem studies reported in this field. By so doing, we hope to provide a better description and understanding of the extent and nature of both the astrocytic and microglial response, which in turn could lead to modifications in the way these therapeutic interventions are delivered.